The wood of five species of Zanthoxylum L. (rutaceae) with distribution in Mexico - Arenas Flores, Fernanda; Andrés-Hernández, Agustina Rosa; Terrazas, Teresa; Castañeda, Carlos (Instituto de Ecología, A.C., 2016)
Wood anatomy of five species of Zanthoxylum is described and compared. Qualitative and quantitative characters were analyzed through multivariate analyses to identify wood characters that permit to distinguish among species or to group them in the recognized sections within the genus. The species shared the diagnostic wood character for Zanthoxylum as of vessel wall thickness < 4 µm, intervessel pits < 6 µm, except for Z. hidalgense, libriform fibers, and parenchyma in marginal bands. The semiring-porosity distinguished the studied species of other Zanthoxylum species. The occurrence of druses in vessels and septate fibers are reported for the first time for the genus. The results of principal component analysis and the phenogram support the recognition of the five species studied based con a unique combination of wood characters; however, wood characteristics do not always support inclusion in the current sections. Zanthoxylum purpusii is recognized by the vertical traumatic canals and septate fibers; Z. arborescens, Z. purpusii and Z. liebmannianum are grouped by parenchyma in marginal bands and biseriate rays. Zanthoxylum hidalgense is the species with the wider vessels, wider and longer fibers as well as taller and wider rays while Z. arborescens and Z. liebmannianum show the narrower vessels and shorter and narrower fibers. Vessel diameter and length and diameter of fibers appear to be related to the vegetation type where the species studied are distributed.